Formative Assessment Practices and Their Effects on Students’ Motivation and English Achievement in Vietnamese High Schools - Quoc Tuan, Tran; Duy Mong Ha, Nguyen; Van Hao, Le (Journal of Education and Teaching (JET), 2026)
This study aimed at exploring formative assessment practices and their effects on students’ motivation and English achievement in Vietnamese high schools. It employed a mixed-method approach to collect quantitative data through questionnaires for both educators and students, and qualitative one through in-depth interviews on five selected educators. Its sample consisted of 418 school leaders, teachers of English and 1829 students randomly selected from 38 high schools in Tien Giang province. Its results showed the feasibility of formative assessment in improving students’ motivation and English achievement. The findings indicated that formative assessment contributed to enhancing learning motivation and improving students’ language skills and knowledge. Noticeably, there were no significant difference in statistics for the educator group (p > .05), but difference for the student one (p < .05), in employing formative assessment on English learning. The study also suggests that teachers should use various kinds of formative assessment in fostering students’ learning motivation and achievement. School leaders should facilitate and encourage teachers to use themfrequently in their teaching as well as monitor their activities to make sure that they are effectively exploited. Besides, policy makers should get feedbacks from Services and schools to adjust policies appropriately to the reality.